1, 2‐Shift of Element‐Centered Groups (RnE) in Carbenoid Anions [RnECF2CFCl]− and its Relevance for Nucleophilic Vinylic Substitution: a DFT Study. Issue 12 (12th August 2016) - Sazonov, Petr K.; Gloriozov, Igor P.; Oprunenko, Yuri F.; Beletskaya, Irina P.
Abstract: The 1, 2‐shift of β ‐substituent to the carbenic or carbenoid centre is one of the primary reaction pathways for these intermediates. In the present work the 1, 2‐shift of various element‐centered groups in carbenoid anions [Rn ECF2 CFCl] – (E=C, N, Si, Ge, Sn, P, As, Sb, S, Se, Te, R=Me) is for the first time examined with the help of density functional theory calculations. The calculations were performed on the models of free carbenoid anions [Rn ECF2 CFCl] – and their Na + and [NMe4 ] + salts. In all cases the 1, 2‐shift of the Rn E‐groups formed by the elements of the third and subsequent periods was calculated to be much more facile than for carbon‐centred groups. Calculated ΔG ≠ are as low as 4–6 kcal/mol for the 5 −th period Me3 Sn‐ and Me2 Sb groups. An even more facile 1, 2‐shift precludes the existence of the corresponding β ‐element substituted carbenes. Periodicity trends, correlation analysis and NBO analysis of the transition state structures were used to discriminate between different intrinsic mechanisms. In free carbenoid anions the main mechanisms of 1, 2‐shift of Rn E‐groups are: a) electrophilic shift of R3 E‐ (E= Si, Ge, Sn) and Ph‐groups; b) nucleophilic shift of RS‐ group c) dyotropic‐type pathway for RS‐, RSe‐, RO‐, R2 N and R3 C‐ groups. In carbenoid ion pairs: a) nucleophilic shift of Rn E‐ (E=Si, Ge, Sn P, As, Sb) and Re(CO)5 ‐ groups; b) nucleophilic substitution involving the lone pair of RS‐, RSe‐ and R2 N‐ groups. Abstract : Carbenoid anions with β‐Men E‐groups (where E – is the third to fifth period metalloid element) can easily rearrange to alkenes, the barriers of 1, 2‐shift of Men E‐group can be as low as 4–6 kcal/mol (for E= Sn, Sb, Te). Compared to the well known 1, 2‐shifts of carbon based groups, the shift of the Men E‐groups is not only more facile, but also more mechanistically diverse. Several distinct 1, 2‐shift pathways are found in the calculations, both of nucleophilic and electrophilic type. migration.